The influence of the Jigsaw cooperative model to increase interest in learning science in fourth grade elementary school students (Quasi-Experimental Research on Class IV Elementary School Science Learning at SDN Kalihurip II) - Dewi, Rinanda; Fitri Nuraeni; Afridha Laily Alindra (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
Basic education is important for building students' knowledge and learning attitudes. Natural Sciences (IPA) is often considered difficult and less interesting by students, so low interest in learning becomes a challenge for educators. This study aims to examine the effect of Jigsaw type cooperative learning model on science learning interest of fourth grade elementary school students. The research used quasi-experimental method with nonequivalent control group design. The research subjects were fourth grade students of SDN Kalihurip II, consisting of 28 students in the experimental class and 28 students in the control class. The experimental class used the Jigsaw model, while the control class used the Picture and Picture model. The results showed that students who learned with the Jigsaw model had a higher interest in learning, with 87% of the interest caused by the Jigsaw model and 13% by other factors. Inferential statistical analysis showed significant differences between the two classes. The Jigsaw model proved effective in increasing students' interest in learning science. This study suggests the Jigsaw model as an alternative to increase students' interest in learning.